Pengaruh Kompetensi, Motivasi Kerja Dan Kompensasi Terhadap Kinerja Pegawai Melalui Kepuasan Kerja Di Dinas Pemadam Kebakaran Kabupaten Garut - Vieny Marita Amalia; Alamanda, Dini Turipanam; Jumiati; Yulia, Hanna (Jurnal ilmiah Manajemen Publik dan Kebijakan Sosial, 2024)
This study aims to analyze the effect of competence, work motivation, and compensation on job satisfaction and employee performance in the Garut District Fire Department. The method used in this study is a quantitative method with the purpose of verification. The research instrument was a questionnaire distributed to Garut Regency Fire Department employees. Furthermore, to analyze the data that has been collected, researchers use Partial Least Squares Structural Equation Modeling (PLS-SEM), which is a statistical analysis tool to test the influence model between predetermined variables. In the next stage, researchers analyze the collected data using tools like WarpPLS. The results showed that work competence and motivation significantly influenced employee job satisfaction. Employees with good competence and high work motivation tend to have higher levels of job satisfaction. In addition, the findings of this study revealed that employee job satisfaction significantly influences employee performance. Employees who are satisfied with their jobs tend to perform better. The implication of this study is to suggest that the management governance of the Garut Regency Fire Department pays attention to developing employee competencies and motivating employees effectively to increase job satisfaction and employee performance. In the context of public services, paying attention to these factors is very important to enhance the organization's quality of service.